Pengaruh Profitabilitas, Ukuran Perusahaan, Kepemilikan Manajemen dan Media Exposure Pada Pengungkapan Corporate Social Responsibility - Permadiswara, Ketut Yoga; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 25 No 1 (2018), 2018)
The emergence of awareness that production activities will indirectly affect the environment eg deforestation, waste disposal, air pollution and so forth. It makes the company obliged to take responsibility for its activities. The purpose of this study is to obtain empirical evidence of the influence of the level of profitability, firm size, management ownership and media exposure on CSR in the annual report of manufacturing companies listed on Indonesia Stock Exchange. The method of determining the sample used is purposive sampling. Number of companies that meet the criteria are 22 manufacturing companies listed on the IDX 2014-2016 year with 66 amount amatan.Teknik data analysis used is Multiple Linear Regression.Based on the analysis, it is known that profitability, firm size and media exposure have a positive effect on disclosure of corporate social responsibility. The results of this study also show that management ownership has no effect on corporate social responsibility disclosure. Keywords :  profitability, firm size, management ownership, media exposure, corporate social responsibility